The paradox of tax competition: Effective corporate tax rates as a determinant of foreign direct investment in a modified neo-Kaleckian model - Ryan Woodgate (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
After demonstrating the empirical relevance of tax competition effects across OECD countries, we incorporate such effects into a Kaleckian model. Corporate tax rates are seen as affecting investment by the effect on the location of multinational enterprise (MNE) investment, not on the total size of worldwide MNE investment. Hence, unlike the neoclassical approach, in our analysis investment is not driven by tax rates affecting the cost of capital, which is objectionable from a post-Keynesian perspective. With this locational qualification in place, we augment a traditional neo-Kaleckian model with the effects of MNE investment and determine under what conditions a country's policymakers can stimulate demand by raising corporate tax rates (via the usual Kaleckian redistribution channel) or lowering tax rates (via the tax competition FDI channel). The result of this exercise shows that our model predicts countries of small economic size will be more likely to engage in tax competition. Moreover, if the usual Keynesian stability condition holds, we can show that the effect of higher corporate tax rates on demand is much more likely to be negative than positive. To see how an interdependent world system of corporate tax rates may interact and develop over time, we use a procedural-based simulation approach using the conditions derived from our modified neo-Kaleckian model to inform the behavioural rules of our simulated policymakers. The simulations show a propensity of corporate tax rates around the world to convergence and to fall in systems with realistic parameter ranges, offering an explanation for the empirical phenomenon of the so-called "race to the bottom" in corporate tax rates. The "bottom" is shown within our model to be a bad equilibrium, from which tax coordination is proposed as a means of escape.
Keywords: E11; E12; E62; F55; H25; 330; tax competition; Kalecki; multinational enterprises; race to the bottom; simulation; foreign direct investment; policy coordination